From reluctance to addiction: the impact of reflective journals on Qatari undergraduate students' learning. Issue 2 (3rd March 2020) - Ahmed, Abdelhamid M.
ABSTRACT: Reflective journals are used to develop students' writing skills, assess reflection level, gather research data, promote teachers' professional development, promote instructional practices, and affect students' learning. However, little research explored the impact of reflective journals on undergraduate students' learning and its challenges in an English writing course. The current study fills the gap in the literature by exploring Qatari female undergraduate students' perspectives of reflective journals in an English writing course and identifying their challenges with using reflective journals. Social constructivism and Gibb's reflective cycle informed the theoretical framework of the study. Using a case study methodology, the researcher designed a reflective journal based on Gibbs' reflective cycle. Accordingly, reflective journals, written by 55 Qatari female undergraduate students, were collected and qualitatively analysed using thematic content analysis. Findings revealed that students experienced the following learning moments in their English writing course: engaging, invaluable, surprising, challenging, novel, perplexing, worrying, enlightening, and transferrable. Moreover, participants reported a number of benefits and challenges of using reflective journals that are peculiar to the Qatari context. Implications for using reflective journals in higher education are provided.